Pengaruh Corporate Governance Terhadap Luas Pengungkapan Integrated Reporting dan Implikasinya terhadap Nilai Perusahaan - Mandalika, Lucky; Hermanto, Hermanto; Handajani, Lilik (E-Jurnal Akuntansi, 2020)
The objective of this study is to analyze the effect of corporate governance on the extent of integrated reporting (IR) disclosure and its implications for corporate value in public companies for the 2017-2018 period. Corporate governance is proxied by the proportion of independent commissioners, audit committee expertise, frequency of audit committee meetings, institutional ownership, and foreign ownership.The results showed a significant positive effect on the frequency of audit committee meetings on IR disclosure area. Meanwhile, there is no influence of the proportion of independent commissioners, audit committee expertise, institutional and foreign ownership on the extent of IR disclosure. Other findings also reveal that there is no influence of IR disclosure on corporate value. For managers, this research implies IR disclosure to improve company performance. For investors, IR are expected to help in making investment decisions. Keywords:  Integrated Reporting; Corporate Governance; Corporate Value.